2010
DOI: 10.1002/ptr.3322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginsenosides Rg3 and Re on glucose transport in mature 3T3‐L1 adipocytes

Abstract: Ginsenosides, the active component of Panax ginseng, have been shown to evidence a variety of biological activities associated with hyperglycemia, obesity and type 2 diabetes mellitus. This study evaluated the effects of the ginsenosides, Rg3 and Re, on glucose uptake and the glucose transport system in mature 3T3-L1 cells. The results demonstrated that the glucose uptake of ginsenosides Rg3 and Re at concentrations of 1-10 µM significantly increased by approximately ∼10% and ∼12%, respectively. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…They found that the active ingredients in this plant, such as ginsenosides Rg3 and Re, were effective with respect to glucose uptake via insulin-dependent pathways because it increased the expression of GLUT4, insulin receptor substrate 1, and PI3K (39).…”
Section: The Enhancement Of Glucose Uptake Through the Upregulation Omentioning
confidence: 99%
“…They found that the active ingredients in this plant, such as ginsenosides Rg3 and Re, were effective with respect to glucose uptake via insulin-dependent pathways because it increased the expression of GLUT4, insulin receptor substrate 1, and PI3K (39).…”
Section: The Enhancement Of Glucose Uptake Through the Upregulation Omentioning
confidence: 99%
“…Where else Re and Rg3 demonstrated the evidence of glucose uptake in mature 3T3-L1 cells. Ginsenoside Rg3 was studied on PPARg that proved to work as anti-obese compound in 3T3-L1 cell line 6,25,26 . Therefore, this manuscript shows that, although we selected 12 ginsenosides at the beginning from that considering the compounds having binding interaction, we selected only F2 for experimental studies, which may be used for PPARg inhibition to confirm our Insilco hypothesis.…”
Section: Molecular Interaction Results Of Pparg With Ginsenosidesmentioning
confidence: 99%
“…Ginsenoside Rg3 suppresses cytokine expression in Ab42-treated BV-2 cells and blocks the nuclear factor (NF)-jB signaling pathway. Antiobesity and antidiabetic effects of ginsenoside Rg3 have been demonstrated in several models [21,42,50]. In 2009, Hwang et al [21] described the antiobesity activity of ginsenoside Rg3 by demonstrating its effect on the regulation of AMP-activated protein kinases and the peroxisome proliferator-activated receptor (PPAR)-c in 3T3-L1 cells.…”
Section: Biological Activitiesmentioning
confidence: 98%
“…It has been well documented that Rg3 exerts a protective effect against cancer [15,41,68], neurotoxicity [24], and metabolic disease [21,42,50] (Table 1). In regard to its anticancer properties, an increase in cancer cell apoptosis is a major outcome [22,41,52].…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation